2022
DOI: 10.1029/2021jd036233
|View full text |Cite
|
Sign up to set email alerts
|

On the Evolution of a Long‐Lived Mesoscale Convective Vortex that Acted as a Crucial Condition for the Extremely Strong Hourly Precipitation in Zhengzhou

Abstract: Torrential rainfall is one of the most severe natural disasters in China, which causes severe economic losses and heavy casualties every year (Song, 2018;. North China is a major rainfall region for the east of China (Tao, 1980) with most of its rainstorms appeared in the period from late July to early August.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 34 publications
(76 reference statements)
2
26
1
Order By: Relevance
“…From 0600 to 0900 UTC on 20 July, within the key region of the MCV (a 2° × 2° box; Fu, Zhang, et al, 2022; Fu, Tang, et al, 2022), strong convergence dominated below 650 hPa (Figures 4a–d), and at the levels above 650 hPa, intense divergence appeared. This vertical configuration was conducive to maintaining upward motions.…”
Section: Analyses On the Mesoscale Convective Vortexmentioning
confidence: 99%
See 1 more Smart Citation
“…From 0600 to 0900 UTC on 20 July, within the key region of the MCV (a 2° × 2° box; Fu, Zhang, et al, 2022; Fu, Tang, et al, 2022), strong convergence dominated below 650 hPa (Figures 4a–d), and at the levels above 650 hPa, intense divergence appeared. This vertical configuration was conducive to maintaining upward motions.…”
Section: Analyses On the Mesoscale Convective Vortexmentioning
confidence: 99%
“…During 17 to 22 July, 2021, an extreme heavy rainfall event (HRE) occurred in Henan Province (hereafter “21.7” HRE). As released by the government of Henan Province, more than 14.78 million people across the province have been affected with 398 dead or missing, and a direct economic loss of up to ~120 billion Yuan has been caused (Fu, Tang, et al, 2022; Fu, Zhang, et al, 2022; Li et al, 2022; Yin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The maximum hourly rainfall in Zhengzhou, the provincial capital, reached 201.9 mm. The event resulted in more than 300 casualties and large amounts of damage to properties (Chen et al., 2022; Yin et al., 2022) and attracted widespread attention from researchers (Fu et al., 2022; Nie & Sun, 2022). The ensemble‐based analysis and numerical simulations in the previous two parts of this study (Xu, Duan, Li, et al., 2022; Xu, Duan, Xu, 2022) suggested that the southerly flow had a key role in the water vapor, energy, and the intensity and location of the convergence zone in the Henan region, and also significantly affected the intensity of precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, the moisture converged mainly over Henan Province, where the topography is characterized by high mountains in the west (Taihang Mountains and the Funiu Mountains) and is thus favorable for ascending motion and corresponding heavy rainfall (Liang et al., 2022; Ran et al., 2021; Yin et al., 2022). Both strong ascending motion and abundant moisture supply were responsible for the occurrence of extreme flooding (Fu et al., 2022; S. Zhang et al., 2022). The regional numerical model, to some extent, can reproduce synoptic systems and extreme rainfall (X. Y. Wang et al., 2022; Yin et al., 2022).…”
Section: Introductionmentioning
confidence: 99%